The actuarial implications of increasing the compulsory retirement age on the government pension scheme in Malaysia / Rose Irnawaty Ibrahim - Ibrahim, Rose Irnawaty (2009)
Many researches on life expectancy have been done, and for most countries it is shown to be increasing. Since the life expectancy at a particular age tends to increase over time for male and female, the mortality risk tends to be lighter over time. Therefore it is expected that pensioners will live longer and thereby cause an increase in pension liabilities to the government. Many countries are now facing a problem of an increase in pension costs, and are looking for solutions to this problem. The most common solutions used are to equalize the retirement age for male and female and to raise the retirement age up to 65 years old. On 1st October 2001, the Malaysia government had extended the compulsory retirement age from 55 to 56 years old with an option to retire earlier. And up to date, the Malaysia government had again extended the compulsory retirement age to 58 years old with an option to retire earlier, which was enforced from 1st July 2008.